Faktor yang Mempengaruhi Kualitas Tidur Mahasiswa Fakultas Kedokteran Universitas Halu Oleo - Haryati Haryati; Siti Patma Yunaningsi; Junuda RAF (Jurnal Surya Medika (JSM), 2020)
Sleep is one of the basic human needs that can affect the quality of life and health. Poor sleep quality can result in decreased physiological and psychological health. Purpose: This study aims to determine the factors that affect the sleep quality of medical students of Halu Oleo University. The study design was using quantitative research with a cross-sectional approach. The sample of this study were 174 medical students of Halu Oleo University in the second and third academic years. The sampling technique was using Proportional Random Sampling. Data on sleep quality obtained by using the Pittsburgh Sleep Quality Index (PSQI) questionnaire and data analysis was using a chi-square statistical test with a confident interval of 95% (alpha = 0.05). The median age of respondents was 20 (range 18-21) years and 127 (73%) of the participants were females. A student with high physical activity was 112 (64.4%), sleep pattern in the good category as much as 98 (56.3%), and students with emotional stress in the low category were 120 (69.0%). More than half of students (89.1%) have poor sleep quality. The bivariate analysis showed that the factors that affect sleep quality were sleep patterns (p-value = 0.019) and emotional stress (p-value = 0.021). Student physical activity was not statistically affected sleep quality (p-value = 0.519). The sleep quality of medical students of Halu Oleo university were affected by sleep patterns and emotional stress.